AKUNTABILITAS PENGGUNAAN KEUANGAN DESA (Studi Laporan Pertanggungjawaban Penggunaan APBDes di Desa Alam Panjang Kecamatan Rumbio Jaya Kabupaten Kampar Tahun 2018) - Rahmat Budianto; Rury Febrina (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
This study examines and analyzes the accountability report on the use of village finances in Alam Panjang Village, Rumbio Jaya District, Kampar Regency. In the use of village finances, accountability reports are required as a form of good governance, based on Presidential Regulation No. 29/2014 concerning the Performance Accountability System for Government Agencies, so that governance is running well, effectively and efficiently. Data collection techniques in this study used observations or field observations, interviews and documentation. The results showed that the village government of Alam Panjang had delivered village financial reports in an accountability manner, both vertically (to the regent) and horizontally (to the community) which were submitted through various community forums. However, even though the accountability report has followed the existing regulations / regulations, monitoring and evaluation is also needed in the use of village finances, so that village finances can be of benefit to village development and improve community welfare.